PENGEMBANGAN KETRAMPILAN WIRAUSAHA SOSIAL BAGI SISWA SMP AL JANNAH PONDOK RANGGON, JAKARTA TIMUR - Halim Putera Siswanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
The community engagement team of Universitas Tarumanagara so far has been routinely involved in the entrepreneurship construction program in the ‘Al Jannah’ Junior High School. Several workshop activities that have been conducted by this team are expected to be continually provided to the students in this school. During the organization of these community engagement activities, besides providing the material regarding entrepreneurship, the team also invited some speakers from various fields of entrepreneurship. In the entrepreneurship construction program, the school also attempted to equip the students with various entrepreneurial skills, starting from the delivery of materials about how to seek business opportunities, recognizing the self-potentials, to those about direct knowledge transfer from the real entrepreneurship. During this pandemic, the school attempt to seek entrepreneurs who are willing to be the speakers to share their entrepreneurial experiences to the students, either through online or offline ways. On this occasion, the team of Universitas Tarumanagara was invited to conduct an activity regarding the social entrepreneurship. Besides delivering the material about social entrepreneurship, this kind of activity also involved some speakers experiencing the business in this field. In order to accommodate this necessity, the team invited Ranny Kreasi that produces handicrafts from used-newspaper materials as the speaker.Keywords: social entrepreneurship, SME, creative product, recycled material Tim PKM Universitas Tarumanagara selama ini secara rutin turut terlibat dalam program pembinaan Kewirausahaan di SMP Al Jannah. Beberapa kegiatan workshop yang pernah dilakukan oleh tim PKM Universitas Tarumanagara secara kontinyu diharapkan dapat terus diselenggarakan pada siswa di sekolah ini. Dalam penyelenggaraan kegiatan PKM, tim PKM Universitas Tarumanagara selain memberikan materi seputar Kewirausahaan juga mengundang sejumlah narasumber dari wirausaha di berbagai bidang. Dalam program pembinaan Kewirausahaan ini, pihak sekolah berupaya membekali siswa dengan berbagai ketrampilan berwirausaha, mulai dari penyampaian materi seputar mencari peluang usaha, mengenali potensi diri, hingga materi-materi yang sifatnya transfer knowledge dari wirausaha langsung. Saat pandemi, sekolah mencoba mencari wirausaha yang bersedia menjadi narasumber untuk menularkan pengalaman berwirausaha mereka bagi para siswa baik secara daring maupun luring. Pada kesempatan kali ini, tim PKM Universitas Tarumanagara diminta untuk memberikan kegiatan dengan materi utama berupa Kewirausahaan Sosial. Selain menyampaikan materi mengenai Kewirausahaan Sosial, diharapkan kegiatan PKM juga melibatkan narasumber wirausaha yang menggeluti bisnis di bidang ini. Untuk mengakomodasi kebutuhan ini, tim PKM mengundang narasumber Ranny Kreasi yang memproduksi kerajinan tangan dari bahan baku koran bekas.Kata kunci: kewirausahaan sosial, UKM, produk kreatif, bahan daur ulang